2019
DOI: 10.1038/s41525-019-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing identifies clonal structure of T-cell repertoires in patients with adult T-cell leukemia/lymphoma

Abstract: The diversity of T-cell receptor (TCR) repertoires, as generated by somatic DNA rearrangements, is central to immune system function. High-throughput sequencing technologies now allow examination of antigen receptor repertoires at single-nucleotide and, more recently, single-cell resolution. The TCR repertoire can be altered in the context of infections, malignancies or immunological disorders. Here we examined the diversity of TCR clonality and its association with pathogenesis and prognosis in adult T-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…In addition, longitudinal analysis of TCR repertoires demonstrated a correlation of the TCR clonal expansion with HTLV-1 proviral load. ATLL patients also showed monoclonal TCRs compared with ACs, and clonality data observed based on TCR repertoires were completely consistent with clonality analysis based on provirus integration sites (Rowan et al 2016;Farmanbar et al 2019). Recently, Tax 301-309 -specific CTL in HLA-A*2402 ATLL patients and ACs shared highly restricted TCR repertoires by the single-cell analysis (Ishikawa et al 2017).…”
Section: T Cell Receptor Repertoire Analysissupporting
confidence: 70%
“…In addition, longitudinal analysis of TCR repertoires demonstrated a correlation of the TCR clonal expansion with HTLV-1 proviral load. ATLL patients also showed monoclonal TCRs compared with ACs, and clonality data observed based on TCR repertoires were completely consistent with clonality analysis based on provirus integration sites (Rowan et al 2016;Farmanbar et al 2019). Recently, Tax 301-309 -specific CTL in HLA-A*2402 ATLL patients and ACs shared highly restricted TCR repertoires by the single-cell analysis (Ishikawa et al 2017).…”
Section: T Cell Receptor Repertoire Analysissupporting
confidence: 70%
“…Other emerging predictive biomarkers such as tumor mutational burden (TMB) ( 9 , 10 ), signatures of a T cell inflamed tumor microenvironment (TME) either alone ( 10 ) or in combination ( 11 ), and neoantigen load ( 12 14 ) are still undergoing clinical trials. In addition, T cell receptor (TCR) diversity has been used as a biomarker to monitor the clonal expansion of T cells in breast cancer, glioma, cervical cancer, and leukemia/lymphoma ( 15 18 ). Further efforts both to exploit the utility of these biomarkers and to search for additional ones are still ongoing.…”
Section: A Change In the Landscape Of Biomarkers Discoverymentioning
confidence: 99%
“…Alternatively, variant allele frequency measurements of specific ATL genetic abnormalities provide an alternative measurement of clonal outgrowth of ATL (Farmanbar et al, 2018). Laydon et al (2014) and Farmanbar et al (2019) also reported quantification of HTLV-1 clonality using TCR diversity analysis. However, we have identified subjects in whom two or more TCR gene rearrangements are present within a population of ATL cells with a single proviral integration site (Rauch et al, 2019).…”
Section: Biomarkers For Atlmentioning
confidence: 99%